Performance of predictive control for a continuous horizontal fluidized bed dryer. (July 2022) - Gagnon, Francis; Desbiens, André; Poulin, Éric; Bouchard, Jocelyn; Lapointe-Garant, Pierre-Philippe
Abstract: Advanced process control can benefit to the operation efficiency and quality of tablets produced by wet granulation lines. Following the development of a new fully continuous fluidized bed reactor as a potential substitute for the current batch dryer design, this paper examines the energy and product quality performances of two predictive control strategies using an experimentally validated simulator. The first one proposes an economic model predictive controller explicitly minimizing the dryer energy consumption. The second one follows the same objective, but uses a simpler classical predictive control framework implementing targets on manipulated variables to drive them toward low energy consumption operating points. Both controllers lead to similar performances, and consume about 20% less energy than a reference feedback scheme without manipulated variable setpoints. Results also show that tracking the product quality attribute significantly benefits from a feedforward action because of the long residence time. This article addresses a subject little explored by the literature, the control of continuous fluidized bed dryers, and clearly demonstrates that a standard linear strategy can reduce the operating costs with an appropriate design. Highlights: Predictive control is applied on a simulated continuous fluidized bed dryer. An economic model predictive controller (EMPC) minimizes the energy consumption. A more standard predictive controller (MPC) also aims for low-energy actions. Both EMPC and MPC results in low-energy operations. Feedforward compensation improves the product quality in both cases.